2007
DOI: 10.1530/eje-07-0059
|View full text |Cite
|
Sign up to set email alerts
|

Circulating obestatin levels and the ghrelin/obestatin ratio in obese women

Abstract: Objective: We measured blood levels of obestatin, total ghrelin, and the ghrelin/obestatin ratio and their relationship with anthropometric and metabolic parameters, adiponectin and insulin resistance, in overweight/obese and normal-weight women. Design: Outpatients Unit of Endocrinology of the S Orsola-Malpighi Hospital of Bologna, Italy. Methods: Fasting obestatin, ghrelin, adiponectin and lipid levels, fasting and glucose-stimulated oral glucose tolerance test insulin, and glucose levels were measured in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 34 publications
10
51
0
6
Order By: Relevance
“…Therefore, the assumption that systemic total ghrelin levels reflect acyl ghrelin secretion should be made with caution (Gauna et al, 2007). For instance, fasting plasma total ghrelin (Cummings et al, 2002a;English et al, 2002;Rigamonti et al, 2002;Shiiya et al, 2002;Erdmann et al, 2005;Korner et al, 2005Korner et al, , 2006le Roux et al, 2005b;Engström et al, 2007;Guo et al, 2007;Vicennati et al, 2007;Huda et al, 2009;), des-acyl ghrelin (Rodríguez et al, 2009), and obestatin (Guo et al, 2007;Nakahara et al, 2008) concentration were lower in obese than lean subjects, whereas acyl ghrelin concentration was higher in obese persons (Rodríguez et al, 2009). In addition, obese persons showed lower expression of GHS-R in omental adipose tissue (Rodríguez et al, 2009).…”
Section: A Obesitymentioning
confidence: 98%
“…Therefore, the assumption that systemic total ghrelin levels reflect acyl ghrelin secretion should be made with caution (Gauna et al, 2007). For instance, fasting plasma total ghrelin (Cummings et al, 2002a;English et al, 2002;Rigamonti et al, 2002;Shiiya et al, 2002;Erdmann et al, 2005;Korner et al, 2005Korner et al, , 2006le Roux et al, 2005b;Engström et al, 2007;Guo et al, 2007;Vicennati et al, 2007;Huda et al, 2009;), des-acyl ghrelin (Rodríguez et al, 2009), and obestatin (Guo et al, 2007;Nakahara et al, 2008) concentration were lower in obese than lean subjects, whereas acyl ghrelin concentration was higher in obese persons (Rodríguez et al, 2009). In addition, obese persons showed lower expression of GHS-R in omental adipose tissue (Rodríguez et al, 2009).…”
Section: A Obesitymentioning
confidence: 98%
“…Circulating obestatin concentrations have been reported to be either reduced (Anderwald-Stadler et al 2007;Nakahara et al 2008) or, more frequently, increased (Guo et al 2007;Prodam et al 2011;Reinehr et al 2008;Vicennati et al 2007) in obesity. Based on available data, it is difficult to explain these contrasting findings that seem to depend mainly on sample size, age, and ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Changes in the concentrations of these hormones, and in the ghrelin/obestatin ratio, may be risk factors for obesity and hypertension. 8 Ghrelin is a peptide hormone secreted primarily from the stomach and duodenum; it is a stimulant of appetite and increases adiposity in rodents. 9 However, many studies have shown that obesity is associated with a decrease in circulating ghrelin.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition, obestatin has been shown to be positively correlated with ghrelin. 8 This suggests that levels of both obestatin and ghrelin may be altered in obesity and insulin resistance. Obestatin has been reported to decrease vascular cell adhesion molecule-1 expression in endothelial cells when stimulated with tumour necrosis factor-a, and to increase oxidized low-density lipoprotein binding to macrophages.…”
Section: Introductionmentioning
confidence: 99%